Physiology and pathology of the mammary gland in women in different periods of life (menopausal period and pregnancy) - Wróbel, Andrzej; Putowski, Lechosław; Gogacz, Marek; Semczuk, Andrzej; Gałczyński, Krzysztof; Kulik-Rechberger, Beata; Rechberger, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Knowledge of physiology of the mammary gland help us understand pathological processes which can occur in this organ, for example carcinogenesis. The results of epidemiological studies indicate an increased incidence of breast cancer in women receiving sex steroids, but the data concerning this issue are not unequivocal. The results of WHI (Women Health Initiative) and HERS (Heart and Estrogen/Progestin Replacement Study) studies point out to an elevated risk of neoplasia in the mammary gland among women taking hormone replacement therapy, which evokes a great deal of concern, uncertainty and fear both among doctors and patients. This fear should be replaced by the algorithm of professional medical management and a suitable choice of therapy in relation to a woman’s age, genetic load, history of diseases and expected benefits. Directing a therapeutic option to the patient and supporting it with scientific data on HRT can convince women that the treatment will prevent, to a large extent, fractures, depression, Alzheimer’s disease, colon cancer, stroke and heart attack. The risk of possible breast cancer death is much lower than compared to the affliction caused by estrogen depletion during early menopause. In the following review we present data which deal with physiology of the mammary gland in different periods of the woman’s life, especially menopause. Moreover, the molecular mechanisms that may potentially play a role in neoplasia are discussed.